2014
DOI: 10.1590/s1679-45082014ao2844
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol sclerotherapy of head and neck venous malformations

Abstract: Objective:This retrospective study evaluated the results of sclerotherapy with low doses of ethanol for treatment of head and neck venous malformations.Methods:We treated 51 patients, 37 females. Median age was 23 years. Patients were treated with percutaneous intralesional injection of alcohol every two weeks and followed up prospectively for a median period of 18 months. Most lesions affected the face and cosmetic disfigurement was the most frequent complaint.Results:We performed a median of 7 sessions of sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Most included studies used a single sclerosing agent for each vascular malformation, while the remainder used a combination of them. Five studies reported outcomes of bleomycin sclerotherapy, 10 studies reported outcomes of ethanol sclerotherapy, 7 studies reported outcomes of STS sclerotherapy, 4 studies reported outcomes of ethanolamine 4 (2011) 0.409 (0.204, 0.615) Kishi et al 16 (2014) 0.979 (0.922, 1.036) Lamba et al 17 (2012) 0.286 (0.049, 0.522) Lee et al 18 (2009) 0.324 (0.215, 0.433) Orlando et al 22 20140.275 (0.152, 0.397) Spence et al 29 20110.972 (0.896, 1.048) Su et al 32 20100.933 (0.870, 0.996) Wang et al 33 20170.333 (0.132, 0.535) Wang et al 34 20 (2009) 0.391 (0.192, 0.591) Meng et al 21 20140.163 (0.052, 0.273) Songsaeng et al 28 20150.576 (0.407, 0.744) Zhao et al 35 sclerotherapy, and 4 studies reported outcomes of pingamycin sclerotherapy. In 11 studies either multiple agents were used and we could not separate outcomes by agent or other sclerosing agent including OK-432 were used.…”
Section: Literature Searchmentioning
confidence: 99%
“…Most included studies used a single sclerosing agent for each vascular malformation, while the remainder used a combination of them. Five studies reported outcomes of bleomycin sclerotherapy, 10 studies reported outcomes of ethanol sclerotherapy, 7 studies reported outcomes of STS sclerotherapy, 4 studies reported outcomes of ethanolamine 4 (2011) 0.409 (0.204, 0.615) Kishi et al 16 (2014) 0.979 (0.922, 1.036) Lamba et al 17 (2012) 0.286 (0.049, 0.522) Lee et al 18 (2009) 0.324 (0.215, 0.433) Orlando et al 22 20140.275 (0.152, 0.397) Spence et al 29 20110.972 (0.896, 1.048) Su et al 32 20100.933 (0.870, 0.996) Wang et al 33 20170.333 (0.132, 0.535) Wang et al 34 20 (2009) 0.391 (0.192, 0.591) Meng et al 21 20140.163 (0.052, 0.273) Songsaeng et al 28 20150.576 (0.407, 0.744) Zhao et al 35 sclerotherapy, and 4 studies reported outcomes of pingamycin sclerotherapy. In 11 studies either multiple agents were used and we could not separate outcomes by agent or other sclerosing agent including OK-432 were used.…”
Section: Literature Searchmentioning
confidence: 99%
“…Venous malformations are the most common slow-flow vascular malformations in the head and neck region. 1 They might occur anywhere in the body and show a predilection to the head and neck region. 2 When found in the upper airway, the patient might present with stridor, hoarseness, and difficulty breathing in the supine position.…”
Section: Discussionmentioning
confidence: 99%
“…11 Pure ethanol is the most effective sclerosing agent available, but it can be associated with systemic complications at high doses. 12 The direct contact of pure ethanol with the vascular endothelium will promote protein denaturation, vessel wall necrosis, and disruption of erythrocytes, leading to thrombosis and fibrosis. 13 Detergent-based sclerosants will lead to organized thrombus, endothelium denudation, inflammation, and permanent luminal occlusion.…”
Section: Introductionmentioning
confidence: 99%